Challenges in SAFe® Methodology implementation from the perspective of Project Leadership roles - Solakuja, Jennika (My University, 2024)
Agile as a methodology is a broad concept that today includes several frameworks. Over time, these frameworks have evolved to meet the needs of companies of different sizes and to lead agile software development. Since then, this Agile working methodology has expanded into a general management model in an increasing number of organizations, as it has been used to observe improved transparency, adherence to project budgets, and improved self-direction of personnel. However, many organizations were managed with traditional project management methods for y, decades the transition to Agile has not been an easy experience for many organizations. This master thesis focuses on exploring the Agile methodology framework Scaled Agile Framework SAFe challenges at the managerial level. The study has been carried out as a qualitative study and the aim of the study has been to independently identify the challenges faced by people in managerial positions in their daily work with the SAFe framework The data for the study has been collected by interviewing seven people who have worked in managerial/leadership positions. The interviewees' experience of working with the SAFe framework has been verified before the interviews. The interview method followed a semi-structured interview model. Before the interviews, the interviewees were provided with a question frame that they were able to familiarise themselves with on their own time. During the interviews, the interviewees were asked more detailed questions for their answers when it was deemed necessary. In the interviews, both the benefits and the problems of SAFe emerge. The interviewees explain how SAFe helps achieve the benefits it promises, but some benefits are not materialized due to partial or incorrect implementation of the framework. Human factors, such as established work habits and previous methods, are also highlighted as challenges. The interviews also underscored the importance of training and continuous support in daily work to properly implement the framework within organizations. Additionally, leading different parts of the organization in varying ways can conflict with the SAFe method, such as traditional budgeting, which does not fit with SAFe adaptive and iterative practices. Many of the challenges highlighted in the interviews have been addressed in the SAFe 6.0 update, which is where the discussion of this research concludes.

Agile-menetelmänä on laaja käsite, joka nykyään sisältää useita viitekehyksiä. Ajan myötä nämä viitekehykset ovat kehittyneet vastaamaan eri kokoisten yritysten tarpeita ja auttamaan johtamaan ketterää ohjelmistokehitystä. Sittemmin nämä ketterät työskentelymenetelmä ovat laajentunut yleiseksi johtamismalleiksi yhä useammissa organisaatioissa, sillä niiden avulla on havaittu että voidaan saavuttaa parantunutta läpinäkyvyyttä, projekti budjetissa pysymistä ja henkilöstön parempaa itseohjautuvuutta. Monet organisaatiot ovat kuitenkin hallinneet organisaatioita isossa kuvassa perinteisiä projektijohtamisen menetelmiä hyödyntäen vuosikymmenien ajan, ja siirtyminen ketterään toimintatapaan ei ole tämän vuoksi ollut helppo kokemus monille organisaatioille. Tämä pro gradu-tutkielma keskittyy Agile-metodologiakehyksen Scaled Agile Framework SAFe haasteiden tutkimiseen projekti/hanke johtamisen tasolla. Tutkimus on toteutettu kvalitatiivisena tutkimuksena ja tutkimuksen tavoitteena on ollut itsenäisesti tunnistaa johtotehtävissä olevien ihmisten kohtaamat haasteet päivittäisessä työssään SAFe-viitekehyksen parissa. Tutkimuksen aineisto on kerätty haastattelemalla seitsemää hanke/projekti johtotehtävissä työskenneltyä henkilöä. Haastateltujen kokemus työskentelystä SAFe-kehyksen kanssa on varmistettu ennen haastatteluja. Haastattelumenetelmä noudatti puolistrukturoitua haastattelumallia. Ennen haastatteluja haastateltaville toimitettiin kysymys runko johon he saattoivat perehtyä ennen haastattelua aikaansa. Haastatteluissa haastateltaville kysyttiin tarkentavia kysymyksiä kun se katsottiin tarpeelliseksi. Haastattelu vastauksissa tulevat esiin niin SAFe-mallin hyödyt kuin myös sen ongelmat. Haastateltavat tuovat esiin kuinka SAFe auttaa saavuttamaan arvolupauksensa mukaiset hyödyt. Osa hyödyistä kuitenkin havaitaan jäävän saavuttamattomiksi osittaisen tai virheellisen mallin käyttöönoton vuoksi. Myös inhimilliset tekijät, kuten vakiintuneet työtavat ja aikaisemmat menetelmät, korostuvat haasteina. Haastatteluiden vastauksista korostui myös koulutuksen ja jatkuvan tuen merkitystä päivittäisessä työssä mallin asianmukaiseksi käyttöönotoksi organisaatioissa. Lisäksi eri osien johtaminen organisaatiosta eri tavoilla voi olla ristiriidassa SAFe-menetelmän kanssa, kuten perinteinen budjetointi, joka ei sovi SAFe-mallin mukautuviin ja iteratiivisiin käytäntöihin. Moniin haastatteluissa esiin nousseisiin haasteisiin on puututtu SAFe 6.0 -päivityksessä, johon tämän tutkimuksen keskustelu päättyy.
Keywords: Keywords: Scaled Agile Framework®, SAFe®, Product Management, Scaled Agile, Large-Scale Agile, Agile Implementation, Project Management Avainsanat: Scaled Agile Framework®, SAFe®, tuote johtaminen, skaalattu ketteryys, ketteryyden laaja skaalaaminen, ketterän käyttöönotto, projekti johtaminen